Total hydrocortisone dosage in extremely low birth weight infants and neurodevelopment up to school age - Taniguchi, Akinobu; Chrétien, Basile; Maeda, Takashi; Ueda, Kazuto; Miura, Ryosuke; Tanaka, Ryuichi; Suzuki, Toshihiko; Muramatsu, Yukako; Kataoka, Erina; Kato, Eiko; Yamamoto, Hikaru; Takemoto, Koji; et al. (Pediatric Research, 2025)
BACKGROUND: An association between total hydrocortisone (HC) dosage in infants with extremely low birth weight (ELBW) and subsequent neurodevelopmental outcomes up to school age remains unclear. METHOD: We conducted a retrospective longitudinal cohort study across eight centers in Japan, including ELBW infants born between 2015 and 2017. We investigated the association between total HC dosage administered up to 36 weeks postmenstrual age and neurodevelopmental outcomes to school age. RESULTS: Linear mixed model analysis showed a significant association between higher HC dosage and lower developmental and intelligence quotient (DQ/IQ) scores. This trend persisted at 6 years of age, suggesting a sustained effect of HC on cognitive outcomes. For every 10 mg increase in HC dosage, IQ scores decreased by 2.82 points (95% CI: -3.89 to -1.06, p = 0.001). The interaction term between HC dosage and time was not statistically significant (0.10, 95% CI: -0.18 to 0.37, p = 0.481), suggesting the association of HC dosage on DQ/IQ did not vary substantially throughout the study period. CONCLUSIONS: We found a relationship between total neonatal HC dosage in ELBW infants and DQ/IQ scores over time that persisted at school age. Clinicians should be aware of this potential dose-dependent effect on neurodevelopmental outcomes. IMPACT: As neonatal dexamethasone administration is known to affect neurodevelopment outcomes, hydrocortisone (HC) is considered an alternative to dexamethasone as a glucocorticoid treatment. In infants with extremely low birth weight (ELBW), a relationship has been noted between total HC dosage and neurodevelopment in early childhood. We confirmed the association between total HC dosage in infants with ELBW and poor developmental and intelligence quotients to school age. Although HC is commonly used in the management of ELBW infants, clinicians should be aware of its potential dose-dependent effects on neurodevelopmental outcomes.